The Influence of Principal’s Leadership and Facilities on Teachers’ Performance - Siti Hajar; Syaiful Eddy; Yessi Fitriani (Journal of Social Work and Science Education, 2026)
This study aims to analyze the influence of principal’s leadership and infrastructure on the performance of public junior high school teachers in Suak Tapeh District, Banyuasin Regency. This study is motivated by the condition of teachers’ performance that still needs to be improved, as seen from low professionalism, teaching motivation, and limited facilities that support the learning process. While previous studies have focused more on motivation, academic supervision, or teacher competence, this study fills the gap in research by simultaneously examining the influence of principal’s leadership and infrastructure in public schools in rural areas. The approach used is quantitative with an ex post facto method on all 105 public junior high school teachers in Suak Tapeh District and used as a saturated sample. Data were collected through a Likert scale questionnaire that has been tested for validity and reliability, as well as documentation. Data analysis was conducted using simple and multiple linear regression using SPSS version 26. The results showed that principal’s leadership has a positive and significant effect of 29.6% on teachers’ performance, while infrastructure has an effect of 31.7%. Simultaneously, these two variables have an effect of 37.8%. These findings confirm that effective leadership and adequate school facilities play a crucial role in improving teachers’ performance. The novelty of this study lies in combining these two variables in the context of secondary schools in rural Banyuasin.